The global effect of exposing bakers' yeast to 5-fluoruracil and nystatin; a view to Toxichip. (February 2016) - Graziano, Sara; Gullì, Mariolina; Maestri, Elena; Marmiroli, Nelson
Abstract: A genome-wide screen of a haploid deletion library of bakers' yeast ( Saccharomyces cerevisiae ) was conducted to document the phenotypic and transcriptional impact of exposure to each of the two pharmaceutical products 5-fluorouracil (an anti-tumor agent) and nystatin (an anti-fungal agent). The combined data set was handled by applying a systems biology perspective. A Gene Ontology analysis identified functional categories previously characterized as likely targets for both compounds. Induced transcription profiles were well correlated in yeast and human HepG2 cells. The identified molecular targets for both compounds were used to suggest a small set of human orthologues as appropriate for testing on human material. The yeast system developed here (denoted "Toxichip") has likely utility for identifying biomarkers relevant for health and environmental risk assessment applications required as part of the development process for novel pharmaceuticals. Graphical abstract: Highlights: The expression profile of selected genes was analyzed by qRT-PCR. A system biology analysis helped to identify molecular targets of 5-FU and nystatin. Biomarkers for health or environmental risk assessment were identified.